An analysis of transient stability using center-of-inertia: Angle and speed - Hashim H.; Zulkepali M.R.; Omar Y.R.; Ismail N.; Abidin I.Z.; Yusof S. (2023)
Instability in the system may cause the rotor angle of the machine to accelerate or decelerate depending on the mechanical power and electrical power; most seriously could result to tripping of the machine This paper evaluates the impact of disturbances and types of loads to system stability using Area-based COI-referred Transient Stability Indexes: COI angle and COI speed. The analysis is carried out using PSSE 32 software on IEEE 118 Bus Test System at system conditions with and without dynamic loads. The network is initially divided into significant areas based on the geographical. 2010 IEEE.